Polis und Politesse: der Diskurs über das antike Athen in England und Frankreich, 1630-1760 - Zabel, Christine (Ancien Régime, Aufklärung und Revolution, 2016)
"This book explores the images and ideas that linked people living in the Early Modern era with ancient Athens. Beginning from the end of the 17th century, a positive view of the ancient city became prevalent. This new ideal was accompanied by the creation of new centers of cultural production that competed with the royal court. The study also examines the rhetoric employed by upwardly mobile groups during the 17th and 18th centuries"--